Extraction of Tannin from Jamblang Leaves (Syzigium cumini) with Ethanol Solvent to Reduce Phenols in Phenol-Formaldehyde in Wood Adhesives - Aprilia, Sri; Bakar, Abu; Fajria, Gebrina Rezky; Yuni, Elza; Amin, Amri; Fitriani, Fitriani; Bilad, Muhammad Roil (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Phenol formaldehyde is one of the adhesives often used in wood processing, such as panels, particle boards, fiberboards, plywood, and others. However, the implementation of phenol formaldehyde adhesive has been greatly limited because of its non-renewability and toxicity. Modifying phenol formaldehyde adhesives is needed to reduce formaldehyde emission by adding tannin to the adhesive mixture. This study aims to extract tannin compounds from Java plum leaves with ethanol as a solvent for adhesive mixture. The adhesive implementation on plywood was also prepared, with various tannin content in the range of 10%-50%. The obtained data from tannin extraction from Java plum leaves are tannin yield, functional groups, total phenolic content, viscosity, and compressive test on plywood. The highest tannin yield and content are 46.70% and 27.88 mg/L, respectively, obtained at the weight ratio 1:5. At the same time, products of tannin-phenol formaldehyde have a viscosity as SNI 1987 standards for wood adhesives, namely in the range of 0.68-0.71 poise, while the result of the compressive strength is in the range of 0.02-0.05 N/mm2 and has met the requirement of SNI 1998 standards. Therefore, the tannin from Java plum leaves is a promising substitution of phenol in phenol formaldehyde in some aspects of the wood processing industry.